Treatment Characteristics and Determinants of Poor Glycaemic Control among Type 2 Diabetes Mellitus (T2DM) Patients Attending Clinics at the Three Selected Health Centres in Suva, Fiji between 2011 a 2016 (Global Journal of Medical Research, 2018)
Introduction and Aim: Type 2 Diabetes Mellitus (T2DM) is a global health problem that is reaching epidemic proportions. It Fiji, it has a high admission rate due to complications and is the number one cause of disease specific mortality. The aim of this study was to determine the proportion of poor glycaemic control level among adult T2DM patients, their treatment characteristics and determinants. Methods: This was a 5-year retrospective medical folder audit on randomly selected folders registered between August 1, 2011 to August 1, 2016 from the three selected health centres in Suva, Fiji who all met the following inclusion criteria: T2DM adults > 18 years old, has recent HbA1c test result in 2017, on treatment for > one year and > 4 clinic visits. A total sample of 338 was derived out of 2,073 T2DM registered during the 5-year period and was calculated using proportionate sampling method. The most recent HbA1c was the parameter used to measure glycaemic control. Logistic regression analysis in SPSS version 22 was used to assess the effect of patient's treatment determinants on glycaemic control with p< .05 considered as significant.
Keywords: treatment characteristics; determinants; glycaemic control; type 2 diabetes; fiji